The comparative assessment indicators of EEG during sleep and wakefulness in patients with resistant locally-associated epilepsy - O. V. Grebenyuk; M. V. Svetlic; V. M. Alifirova; A. A. Burlakov (Бюллетень сибирской медицины)
Substance for investigation serve patient with locally-associated epilepsy (LAE), taking antiepileptic drugs — 151 men. From them — 73 patients with drug-resistant forms of the disease and 78 patients with control epileptic seizure. Spend monitoring indicators of EEG during sleep and wakefulness cycle. In the group of patients with drug-resistant forms LAE significantly detected more frequently epileptiform activity and increase index α-rhythm during sleep in comparison with period wakefulness.